The Image and the Figure : Our Lady of Czêstochowa in Polish Culture and Popular Religion. - Nied1/4wied1/4, Anna (Jagiellonian University Press, 2010)
The image of Our Lady of Czêstochowa is the most famous and the most venerated holy image in Poland. In contemporary Poland the image is a kind of a cultural icon, instantly recognizable and connected with popular symbolic and mythological meanings. Presented in this book is an analysis of beliefs, narratives (great and small stories), myths and rituals. This analysis reveals that for its devotees the image is not merely a material object and a picture - it is perceived, lived and experienced as a real person - figure of Mary - Queen and Mother.